Industry restructuring in the ICT sector – What does labor mobility tell us about skill relatedness and knowledge spillovers? - Tuomo Nikulainen; Mika Pajarinen (The Research Institute of the Finnish Economy (ETLA), 2013)
Industries go through different phases of evolution where old skills become obsolete and new skills arecrucial for the industrial renewal process. Industry evolution is usually addressed from the perspectives of production and exports, leaving one factor largely unexplored: human capital. Industry restructuring isa dynamic process where skills developed in one industry move to other industries as individuals change employers. We argue that the labor flows between industries reveal skill relatedness because individuals move to industries that value their existing skills. We also argue that the labor flows differ between highand low-skill labor. By examining these flows, we can identify spillover effects between industries during restructuring. To address this argument, we analyze all individual-level labor flows originating from the Finnish ICT sector for 1989-2010. This industry sector-level study focuses on three ICT industries (manufacturing, services and software), and we address the differences in labor mobility between the individuals with different professional skill levels. We find several differences in the labor market dynamics over time for each ICT industry and for the different skill levels.
Keywords: J24; J21; J62; 330; labor mobility; skill relatedness; ICT sector; knowledge spillovers